Airport - Perry, Philippa (Wayland Hove, 1990)
"Airport " by Philippa Perry and Stephen Gibbs, published by Hodder Children's Books. This book is part of the "Teamwork" series, which explores various professions and emphasizes the importance of collaboration. In "Airport," readers learn about the different roles and teamwork involved in airport operations, providing an engaging introduction to the aviation industry.